KONSEP PELAKSANAAN LELANG GADAI EMAS PADA PEGADAIAN SYARIAH PERSPEKTIF HUKUM ISLAM - Lubis, Muhlisah (Program Studi Manajemen Bisnis Syariah STAIN Mandailing Natal, 2020)
Trade agreements have grown so rapidly as the business reaches the needs of human life, sometimes the agreement does note meet the provisions of applicable law, and can even occur inequality, similary auctions that generally include the from of buying and selling. Because it is not impossible to happen cheating interests of society in general. To mitigate the terms of islam has provided guidelines for achieving the welfare of the people. The auction according to the understanding of contemporary transaction is known as a from of sale in public goods to the hinghest offer. In islam also gives freedom and breadth of space for the business activites of muslims in order to seek the gift of Allah in the forms of mutually beneficial transactions that occur in the community without violete or seize the rights of others unlawfully. And based on the fatwa of the national No.25/DSN-MUI-III/2002 sharia council on Rahn regarding the mechanism of implementation of mortgage collateral goods are allowed, if Rahin still can not pay off the debt, then the marhun sold forcibly/ executed through the auction according to syari’ah.